PENGARUH DEKRIT PRESIDEN TERHADAP DEMOKRATISASI DI INDONESIA - Hermawan, Sapto; Rizal, Muhammad (Veritas et Justitia, 2022)
Presidential Decree (pronouncement) is made in respons to state emergency. The issue discussed here refers to the question who, when and how state emergency occurs justifying the issuance of such pronouncement.  A different issue in Indonesia is the impact such pronouncement has on democracy, considering that the decree itself it made, arguably, to save democracy in the first place. This has been experienced by Indonesia when the President issued such decree in the past. In addition, using comparative method, the author looks at the use and experience of other countries and how such approach impact democracy.